2006
DOI: 10.1524/ract.2006.94.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ozone on ruthenium species in alkaline medium – Part I: Oxidative dissolution of ruthenium dioxide hydrate

Abstract: Ruthenium / Ozone / Solid dissolution / Ruthenate catalysis / Alkaline medium / Waste reprocessingSummary. Several ruthenium species compounds are typically encountered in waste management from nuclear fuel reprocessing operations. Ozone acting as a strong oxidizing agent in aqueous alkaline medium presents some advantages to dissolve rapidly solid deposits of RuO 2 , xH 2 O formed into process devices, without generating troublesome byproducts or secondary wastes. In this study, a three-phase solid-gasliquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…In previous papers, we reported studies about the oxidative dissolution of ruthenium dioxide hydrate (Part I [22]) and oxidation of ruthenium nitrosyl complexes by ozone in an alkaline medium (Part II [23]). In particular an autocatalytic oxidative dissolution of RuO 2 ·xH 2 O was highlighted: ruthenium dioxide is first oxidized to give ruthenates ions, which are oxidized into perruthenates ions.…”
Section: Introductionmentioning
confidence: 99%
“…In previous papers, we reported studies about the oxidative dissolution of ruthenium dioxide hydrate (Part I [22]) and oxidation of ruthenium nitrosyl complexes by ozone in an alkaline medium (Part II [23]). In particular an autocatalytic oxidative dissolution of RuO 2 ·xH 2 O was highlighted: ruthenium dioxide is first oxidized to give ruthenates ions, which are oxidized into perruthenates ions.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study [10], we showed that the rate of oxidative dissolution of RuO 2 ·xH 2 O particles was inversely related to the particle size. In this study, the RuO(OH) 2 ·xH 2 O deposits completely covered the stainless steel test specimen, and any variation in the quantity deposited simply implied different thicknesses but with the same reactive surface area: 100 cm 2 .…”
Section: Effect Of Deposit Quantity On Oxidative Dissolution Kineticsmentioning
confidence: 82%
“…The variation in the solution potential then diminished on reaching the decontamination plateau. In a previous article [10] we showed that it was possible to monitor oxidative dissolution of RuO 2 ·xH 2 O suspensions by ozone in alkaline medium.…”
Section: Ruo(oh) 2 (S)mentioning
confidence: 99%
See 2 more Smart Citations